Pandangan Hukum Islam Terhadap Putusan Ma No. 721.K/Ag/2015 Tentang Pembagian Waris Bagi Non Muslim - Amir, Muhamad Rizal (Institut Agama Islam Sunan Giri Ponorogo, 2023)
In Islamic inheritance law, religious differences are one of the barriers to obtaining inheritance, this is based on the hadith of the Prophet Muhammad, and in KHI (Islamic Law Compilation) non-Muslims (kafir) do not receive inheritance. The problem is what if an heir is of a religion other than Islam, from that problem the Supreme Court of the Republic of Indonesia issued a decision number: 721K/Ag/2016 which provides an opportunity for heirs of different religions to get a share through mandatory wills. library research library research, namely by taking data from libraries and other print media in the form of: books, journals, newspapers, articles, and magazines to get the best data using a juridical and normative approach. The results of the research analysis are: Islamic inheritance law is the law that regulates the transfer of ownership rights to the inheritance of the heir, the mandatory will is stipulated to give rights or shares of property to relatives or adopted children, and their position includes the classification of Dzauwi Al-Arham or ghoiru inheritance, and because the Supreme Court issued decisions in the law of inheritance of different religions in the case of decision no. 721 K/Ag/2015 is about granting inheritance to non-Muslim heirs by way of mandatory will. based on the decision that the wife of the deceased got 2/3 and her two children who converted to religion got 1/3 of the gono-gini property after paying off her late father's debt. This decision is based on several considerations, first: justice, that a law is applied to uphold justice. second: humanity (inssaniyyah), meaning that laws that do not prioritize humanity are not considered substantially law. And third: the law was created to engineer social, which ends in social welfare